VD_FINDINFO HC / 2010 / 443 vom 27. Mai 2010 - VD Tribunal cantonal (2010)
AVOCAT, HONORAIRES, MODÉRATION, ACTION EN PAIEMENT | 451 ch. 3 CPC, 452 al. 2 CPC, 465 al. 1 CPC, 91 CPC, 92 al. 1 CPC, 92 al. 2 CPC, 94 al. 1 CPC, 94 al. 4 CPC, 50 al. 1 LPAv